التحليل الكمي والكيفي لمحتوي الاحماض الدهنية لزيت الفول السواداني لمنطقة وادي سوف - (:unkn) unknown (My University, 2017)
يعتبر الفكؿ السكداني مف أىـ المصادر الغذائية العالمية, خاصة زيتو. في ىذا العمؿ قمنا بتحميؿ كمي ككيفي لمحتكل الأحماض الدىنية لزيتو باستعماؿ كركماتكغرافيا الطكر الغازم كمستخمصو الميثانكلي باستعماؿ كركماتكغرافيا السائمة . أثبتت نتائج التحميؿ غنى زيت الفكؿ السكداني بالأحماض الدىنية غير المشبعة W6بنسبة عالية مقدرة بػ ,%76ك w9,W3بنسب ضعيفة, أثبتت الخصائص الفيزيككيميائية المدركسة كفاءة عينات الفكؿ السكداني. تـ إستخداـ طريقة كاشؼ فكليف كطريقة كمكريد الألكمينيكـ المكنية مف أجؿ التقدير الكمي لمفينكلات كالفلافكنكيدات لممستخمصات. بالإضافة إلى غناه بالمركبات الفينكلية خاصة الكريستيف( )QRفي جميع العينات . أثبتت دراسة الثكابت الفيزيائية كالكيميائية جكدة الفكؿ السكداني كما اظيرت نتائج اختبارم DPPH ك TACقدرتو المضادة للأكسدة كالتي تفكؽ قدرة المركب المرجعي.Peanut is an important food source in the world .in this work we evaluate this product of El-Oued city by qualitative and quantitative analyze of fatty acids components by gas chromatography and its methanolic extract using liquid chromatography . The results confirmed that the peanut oil rich in unsaturated fatty acids w6 yield 76% and with lower yield of w9 and w3. The physicochemical properties studies confirmed the suitability of the oil of present peanut. FolinCiocalteu reagent and aluminium chloride colorimetric methods were used to estimate total phenolic and flavonoid content of extracts. The results of methanolic extract analysis revealed presence of phenolic content and flavonoids, the existence of Querctin (QR) in all studies samples was observed. In vitro antioxidant activities of all extracts using DPPH and TAC method were significant and stronger than the standards
مذكرة ماستر كيمياء
Keywords: الأحماض الدىنية, زيت الفكؿ السكداني, فينكلات, فلافكنكيدات, كركماتكغرافيا الغاز, كركماتكغرافيا السائؿ, اختبار ,DPPHاختبار .T; Fatty acides , peanut oil, phenol,Flavanoid , gas chromatography, liquid chromatography, DPPH test, test of TAC